2003
DOI: 10.1002/em.10129
|View full text |Cite
|
Sign up to set email alerts
|

Genotoxicity and toxicity of the potential cancer‐preventive agent polyphenon E

Abstract: The potential health benefits of green tea continue to attract public and scientific interests and are attributed in part to polyphenolic catechin constituents. Polyphenon E (Poly E) is a decaffeinated green tea catechin mixture containing about 50% epigallocatechin gallate and 30% other catechins. We evaluated the toxicity and genotoxicity of Poly E by using two in vitro assays: bacterial mutagenesis in a Salmonella typhimurium-E. coli assay and the L5178Y mouse lymphoma cell thymidine kinase (Tk) gene mutati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 41 publications
0
32
0
Order By: Relevance
“…The polyphenon E contains 80% to 98% total catechins by weight; the main component is EGCG, which comprises 50% to 75% of the material. Other catechins are present in levels ranging from f2% to 12% each, including epicatechin, epigallotechin, epicatechin-3-gallate, and gallotechin gallate (23). In this in vitro study, three concentration levels were examined in the cell lines (20,40, and 80 Ag/mL).…”
Section: Discussionmentioning
confidence: 99%
“…The polyphenon E contains 80% to 98% total catechins by weight; the main component is EGCG, which comprises 50% to 75% of the material. Other catechins are present in levels ranging from f2% to 12% each, including epicatechin, epigallotechin, epicatechin-3-gallate, and gallotechin gallate (23). In this in vitro study, three concentration levels were examined in the cell lines (20,40, and 80 Ag/mL).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have demonstrated that tea catechins could suppress the genotoxic activity of various carcinogens with both in vitro and in vivo systems (Kuroda, 1996;Sinha et al, 2005;Isbrucker et al, 2006). Chang et al, (2003) have shown that there is minimal genotoxic concern with a decaffeinated green tea catechin mixture. The antigenotoxic and anticlastogenic activities of the tea are mostly due to its antioxidant activity that inactivates the direct carcinogens.…”
Section: Discussionmentioning
confidence: 99%
“…A green tea preparation (consisting of 85 to 95% total catechins (by weight) and more than 55% EGCG) was negative in the Ames test, the rat micronucleus assay, the UDS test, and the transgenic mouse mutation assay, but positive in the mouse lymphoma mutation assay (FDA, 2006;Chang et al, 2003). In an oral (gavage) carcinogenicity study, the same preparation was administered daily for 26 weeks to p53 transgenic mice at doses up to 500 mg/kg/day.…”
Section: Animal and In Vitro Datamentioning
confidence: 99%